The Effectiveness of Dictation Strategies Toward Students’ Listening Skill of Class X in English Lesson at MA Pancasila Bengkulu City - Iskandar, Toto; Akbarjono, Ali; Febriani, Hanura (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examined the effectiveness of dictation strategies on the listening skill of Class X students in English lessons at MA Pancasila, Bengkulu City. It addresses a research gap in the limited number of studies exploring the use of dictation strategies in senior high school English as a Foreign Language (EFL) contexts. A quantitative approach was employed using a quasi-experimental design with a pre-test and post-test model. The sample consisted of 17 students, divided into two groups: an experimental group (9 students) and a control group (8 students). Listening skill was assessed using two instruments: a fill-in-the-blank listening test and comprehension questions. The treatment was conducted over seven learning sessions using thematic dialogue material. The findings revealed a notable difference in improvement between the two groups. The experimental group’s mean score increased by +15.89 points (from 69.67 to 85.56), while the control group improved by +7.12 points (from 69.63 to 76.75). Although the difference was not statistically significant (t-value 1.27 < t-table 2.131), the substantial practical gains and a decrease in the standard deviation in the experimental group indicated a positive effect of the dictation strategy. These results support the theories of Vandergrift, L. & Goh (2012), who argue that active listening strategies like dictation can enhance students’ focus and comprehension. Moreover, the findings suggest that dictation can help narrow performance gaps among students, leading to more equitable learning outcomes. Therefore, integrating dictation into EFL curricula may serve as an effective alternative strategy for improving listening skills in secondary education.